Contemporary urban planning - Levy, John.M. (New Jersey, 2009)
A best-selling title in the urban planning market, Contemporary Urban Planning provides students with an insider's view of sub-state urban planning including details on the interplay of politics, law, money, and interest groups. This text is exceptional in its coverage of economics, law, finance, and urban governance.
Keywords: City planning - United States